Levantamento e análise de materiais didáticos voltados para o ensino de botânica - Amatuzzi, Laise (Universidade Federal de São Carlos, 2023)
There is a lack of interest from humans towards plants, and that phenomenon gets the name of Plant Blindness. This phenomenon describes how human beings fail to notice the plants that make up the environment, or who believe that plants are merely decorative devices, do not recognize their real importance for the existence and permanence of life in our ecosystems. This also has an affect on education with the devaluation of the teaching of Botany, which ends up being considered uninteresting. Coupled with that, schools offer mostly theoretical classes, which are tiresome and use many scientific names, which again lead to the increase in the botanical blindness phenomenon. Considering the situation, it becomes clear that there is a need to find new ways of teaching science, ways that will value the discipline of Botany. One way that was found was the use of didactic materials to engage and encourage students on their pursuit of knowledge in this field. The goal of this project is to survey and analyze the didactic materials found in the literature. With that established, a research was conducted on the different platforms (Scielo, Google academic, UFSCar Institutional Repository) which resulted in 21 articles. The didactic materials found showed a wide variety of forms, such as: artistic pieces, cartotheque, making of specimens, games, laminate, model/mockup, plants or parts of them, digital resources and videos. The themes also varied a lot among the different works. The didactic materials that were found in more quantity were the games. The analysis showed that the students approved the materials as a way of teaching them. It made them more interested on the subject, and brought an easiness to the study of Botany, showing that these materials are alternatives that should be used.
Survey and analysis of teaching materials focused on botany teaching
Keywords: Ensino de Botânica; Materiais Didáticos; Valorização da Botânica; Jogo Didático; Teaching of Botany; Didactic Game; Didactic Materials; Valuing of Botany; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO